Magnetic Resonance Imaging Versus 3-Dimensional Laser Scanning for Breast Volume Assessment After Breast Reconstruction. Issue 4 (April 2017) - Howes, Benjamin H.L.; Watson, David I.; Fosh, Beverley; Yip, Jia Miin; Kleinig, Pakan; Dean, Nicola Ruth
Abstract : Background: There are several methods available for measuring breast volume in the clinical setting, but the comparability and accuracy of different methods is not well described. The ideal breast volume measurement technique should be low cost, comfortable for the patient, have no ionizing radiation and be non-invasive. Methods: Prospective cohort study comparing a 3-dimensional (3D) laser scanner versus noncontrast magnetic resonance imaging (MRI) for breast volume assessment. Subjects were women undergoing breast reconstruction with autologous fat graft. Both types of scan were performed the day before fat grafting and at 6 months postoperatively. Pearson correlations and Bland-Altman tests were performed to compare the assessment methods. Results: Eighteen patients underwent preoperative breast MRI and 3D laser scanning. Eighteen patients also underwent assessment 6 months after surgery. The total number of breasts scanned for comparison was 36, with a total of 72 comparisons for analysis. There was a strong linear association between the 2 methods using a Pearson correlation ( r 2 = 0.79; P <0.001), and Bland-Altman showed a high level of agreement between the 2 methods. Conclusions: The 3D laser scanning, with an established protocol, was found to be equivalent to non-contrast MRI for the assessment of breast volume. Given the convenience of laser scanning and potential for lower cost compared with MRI, this technique should be considered for quantifying outcomes after complex breast reconstruction when the equipment is available.